Ruthenium-catalyzed meta-C–H bond alkylation of aryl 2-pyridyl ketones. Issue 2 (6th December 2019) - Li, Gang; Jia, Chunqi; Cai, Xiaofeng; Zhong, Lei; Zou, Lei; Cui, Xiuling
Abstract : The first example of meta -selective CAr –H bond functionalization of aryl 2-pyridyl ketones has been developed using [Ru( p -cymene)Cl2 ]2 as the catalyst and alkyl bromide as the coupling reagent. Abstract : The first example of meta -selective CAr –H bond functionalization of aryl 2-pyridyl ketones has been developed using [Ru( p -cymene)Cl2 ]2 as the catalyst and alkyl bromide as the coupling reagent. This development provides an efficient strategy for modifying the meta -position of aryl 2-pyridyl ketone skeletons, which are found in various functional molecules.